Reviewing the W.A.R.A. Treatment Strategies during Covid-19- Its Benefits and Challenges - Deepa Parasar, Vinay Phanidhar T, Naveen Kumar Z, Neeta Mazumdar, Sanjeev Kumar (Journal for ReAttach Therapy and Developmental Diversities, 2023)
COVID- 19 pandemic is a wide chapter that impacts massively on daily people’s lives. People have suffered lots of problems physically for not communicating with others. W.A.R.A. strategy is a good process of serving treatment guidance properly with a virtual process. Mainly, this process supported the people to provide self-regulation abilities and that helped the people in solving their physical issues. Therefore, this study aims to develop this study through showing the key competence of W.A.R.A strategies. Secondary data collection method is involved here for collecting data from several resources. Besides, this study could not collect any irrelevant data on it and the overall process presented appropriate findings based on evaluating the literature review section. Some disadvantages are also included here under the context of W.A.R.A strategies such as the communication gap and many more.